Oil and gas complex of Ukraine: analysis and prevention of electrical traumatism - Pahomov, Roman; Zyma, Oleksandr; Dyachenko, Evgen (Academic journal Industrial Machine Building Civil Engineering, 2019)
The work is devoted to the analysis of injury cases from the electric current influence on the oil and gas complex objects. The principles, the main provisions of the system analysis and the classification of electric traumatism cases at power enterprises are presented. Main causes and patterns of the electric trauma occurrence on dependence of the various production features, as well as for various categories of workers are determined in the article. The structural scheme of the relationship between the elements of the system "man – electrical engineering – production environment" is given. A set of preventive measures and practical recommendations that can be successfully applied to assess occupational risk and reduce the level of injury from electric current in the energy sector of Ukraine is proposed.